2001
DOI: 10.1524/zpch.2001.215.8.1043
|View full text |Cite
|
Sign up to set email alerts
|

The CH + N2 Association Reaction at Low Temperatures: Ab Initio MO/VRRKM-Theory Analysis of Temperature and Pressure Effects

Abstract: Microcanonical Variational RRKM / Rate Constants / Pressure EffectThe microcanonical variational RRKM formalism combined with high level ab initio and density functional calculations has been applied to the reaction of CH( 2 Π) with molecular nitrogen at low and moderate temperatures. The existing experimental T , P-dependent data for T < 1000 K could be theoretically accounted for. Our simulations reproduced very well the strong negative temperature and strong positive pressure effects observed experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(55 reference statements)
1
1
0
Order By: Relevance
“…Similar to Berman and Lin [21] and later Moskaleva and Lin [23], the authors concluded that collisional stabilization of HCN 2 is dominant at low temperatures whereas dissociation of this adduct becomes important at higher temperatures. Similar theoretical analyses were performed at about the same time by Rodgers and Smith [24] and Miller and Walch [25].…”
Section: Introductionsupporting
confidence: 56%
“…Similar to Berman and Lin [21] and later Moskaleva and Lin [23], the authors concluded that collisional stabilization of HCN 2 is dominant at low temperatures whereas dissociation of this adduct becomes important at higher temperatures. Similar theoretical analyses were performed at about the same time by Rodgers and Smith [24] and Miller and Walch [25].…”
Section: Introductionsupporting
confidence: 56%
“…Herbert et al observed that the removal of CH( v = 1) by N 2 is rapid [ k (294 K) = 3.0 × 10 -11 cm 3 molecule -1 s -1 ] and that the rate coefficient for this process shows a moderate negative temperature dependence between 86 and 584 K: when fit to expression II, n was ∼1.2. They attribute the fast removal of CH( v = 1) by N 2 to the formation of the weakly-bound CHN 2 species: the strength of the dative bond between CH and N 2 is approximately 30 kcal mol -1 . Herbert et al suggest that the CHN 2 complex might dissociate before the CH vibrational excitation energy is redistributed to the other modes of the complex.…”
Section: Resultsmentioning
confidence: 99%